Tantrasāra text with English translation - Abhinavagupta 950-1020; Chatterjee, Gautam 1958-; Chatterjee, Gautam 1963- (Varanasi New Delhi Indian Mind, 2015)
Treatise on Trika philosophy of Kashmir Saivism
Includes bibliographical references (pages 581-584)
In Sanskrit (Sanskrit in Devanagari and roman) and translation in English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Kashmir Śaivism -- Early works to 1800; Tantrism -- Early works to 1800; Kashmir Śaivism -- Early works to 1800; Tantrism -- Early works to 1800; Kommentar; Quelle -- 1000-1100